Chlorella pyrenoidosa mitigated the negative effect of cylindrospermopsin-producing and non-cylindrospermopsin-producing Raphidiopsis raciborskii on Daphnia magna as a dietary supplement - Lei, Lamei; Lai, Shuyan; Liu, Wei; Li, Yaokai; Zhang, Huiping; Tang, Yali (Frontiers in Microbiology, 2023)
Feeding effects are crucial for evaluating the capacity of zooplankton to regulate phytoplankton populations within freshwater ecosystems. To examine the impact of the bloom-forming cyanobacteria Raphidiopsis raciborskii, which occurs in tropical and subtropical freshwaters, on the growth of zooplankton Daphnia in relation to toxins, filament length and fatty acid content, we fed D. magna with R. raciborskii only (cylindrospermopsin (CYN)-producing and non-CYN-producing, as the negative controls), Chlorella pyrenoidosa only (as the positive control) and a mixed diet containing R. raciborskii (CYN-producing and non-CYN-producing) and C. pyrenoidosa.Consequently, our findings revealed that the toxic effect of CYN-producing R. raciborskii strains on Daphnia was mitigated by the coexistence of C. pyrenoidosa containing stearidonic acid (SDA, C18:4 ω3) in mixed diets. This was evident in the elevated survival rate compared that from diets containing only R. raciborskii and a significantly higher reproduction and population intrinsic increase rate compared to diets consisting of only R. raciborskii or C. pyrenoidos. Additionally, a strong positive correlation was observed between arachidonic acid (ARA, 20:4ω6) and the population intrinsic increase rate of Daphnia; notably, R. raciborskii strains were found to be rich in the ω6 polyunsaturated fatty acid ARA. These outcomes reinforce the crucial role of polyunsaturated fatty acids in predicting the population increase of crustacean zooplankton, which has long been neglected. Furthermore, our results underscore the potential effectiveness of 2 zooplankton, particularly in temperate lakes, in controlling CYN-producing R. raciborskii populations.